(untitled) (Baghdad Science Journal, 2025)
New series of 2-mecapto benzoxazole derivatives (1-20) incorporated into fused to different nitrogen and suphur containing heterocyclic were prepared from 2-meracpto benzoxazole, when treated with hydrazine hydrate to afford 2-hydrazino benzoxazol (1). Compound (1) converted to a variety of pyridazinone andphthalazinone derivatives (2-4) by reaction with different carboxylic anhydride. Also, reaction of (1) with phenyl isothiocyanate and ethyl chloro acetate afforded 3-phenyl-1,3-thiazolidin-2,4-dione-2-(benzoxazole-2-yl-hydrazone) (6). Azomethines (7-10) were prepared through reaction of (1) with aromatic aldehyde, then (7, 8) converted to thaizolidinone derivatives (11, 12). Treatment of (1) with active methylene compounds afforded derivative (13). Reaction of (1) with CS2 and NaOH gave 1,2,4-triazole derivative (14). Treatment of (1) with p-bromophenancyl bromide afforded another 1,2,4-triazole (15). The reaction of 2-mercapto benzoxazole with chloro acetic acid gave (16) followed by refluxing (16) with ortho-amino aniline giving benzimidazol (17). Moreover, the reaction of 2-mercapto benzoxazole with ethyl chloroacetate afforded (18), and then reaction of (18) with thiosemicarbazide and 4% NaOH leads to ring closure giving 1,2,4-triazole derivative (20). All compounds were confirmed by their melting point, FT-IR, UV-Vis spectra and 1H-NMR spectra for some of them.